The Effect of Moringa oleifera on High Fat Diet and Streptozotocin Induced Diabetic Rats: The Antihyperglycemic Effect of Moringa oleifera - Saad Luty, Raad (Iranian Journal of Pharmaceutical Sciences, 2021)
Moringa oleifera has been used in many regions of the world at the level of folk medicine as a remedy for numerous diseases including the treatment of type 2 diabetes. This study aims to investigate the antidiabetic activity of the methanolic extract of M. oleifera leaves in type 2 diabetes mellitus in animal model induced by fat rich diet and the use of the diabetogenic agent, streptozotocin (STZ) in male Wistar rats. A daily dose of 300 mg/kg of M. oleifera extract (MOE) was administered to diabetic male Wistar rats that had been induced by high fat diet feeding for one month followed by intraperitoneal injection of 40mg/kg of streptozotocin. After three weeks of MOE treatment, blood glucose concentration, lipid profile markers, urea, and creatinine were assayed. Food intake was measured daily and body weight was measured weekly. After three weeks of treatment, MOE significantly decreased the blood glucose of the tested rats, and a marked decrease of triglyceride also was noticed. Regarding renal function indicators, MOE significantly decreased the serum urea level of diabetic rats. However, no change has been noticed in the serum creatinine level in all experimental groups. The findings in the present study suggest that M. oleifera can significantly alleviate hyperglycemia, and hyperlipidemia in diabetic rats. M. oleifera could be a potential treatment of type 2 diabetic patients.